4.1 The idea of dialectical communication in the life of society - 1. Salimov Bakhriddin Lutfullaevich. Professor at Tashkent State Transport University. 2. Eshqo‘ziyev Shahboz G‘ayrat o‘g‘li. Student at Tashkent State Transport University. (Innovative technologies in construction Scientific Journal, 2023)
Аnnotation It is emphasized in the article that all spheres of society, all the processes taking place in it have a dialectical content, that the dialectical content and communication as a whole system apply equally to the society itself and to all spheres within it, whether it is the economic sphere or the political sphere, it cannot be dependent on dialectics. Key words: dialectics, good, evil, human, spirituality. The Danish thinker Søren Kierkegaard, who laid the cornerstone of the creation of the philosophy of existentialism, lived from 1813 to 1855, and lived only 42 years, said that states of indifference, neglect and indifference are vices that upset social relations and they never brought light to humanity. At first glance, these may not seem like bad habits. However, upon deeper reflection, these vices lie at the root of many shortcomings and even evils in society. As Søren Kierkegaard pointed out, “if we imagine the life of most people from the point of view of dialectical indifference, it turns out that it is so far from good (faith) and that there is no high level of spirituality in it. ". If you notice, this commentary by Søren Kierkegaard uses the expression spirituality. Also, the issues that we have considered and analyzed above are related to the concept of spirituality. Take in particular the feeling of restlessness in the human heart, which has been mentioned several times. The human heart expresses internal spiritual experiences and emotions of a person. Processes associated with internal spiritual experiences, feelings, spiritual strength, inner wealth, the inner world of a person as a whole constitute spirituality. Mentioned in a number of philosophical literature. When we get acquainted with the works of Søren Kierkegaard, one of his definitions of spirituality, or more precisely, spiritual life, is expressed as follows: “Everything in spiritual life is dialectic.” One question that arises here is what would have changed if Søren Kierkegaard had used the word “spirituality” instead of the word “spiritual life.” In our opinion, nothing significant would change. Because spirituality manifests itself in spiritual life. There is no need to talk about spirituality if there is no spiritual life. Therefore, we would like to ask you not to be surprised if we sometimes use the terms spirituality and spiritual life together in the following places. At the beginning of our opinion, first of all, it should be emphasized that not only spiritual life, but also all spheres of society, all the processes occurring in it, have a dialectical content. Dialectical content and communication equally apply to society itself as an integral system, and to all spheres within it. Whether it is the economic sphere or the political sphere, it cannot depend on dialectics. In particular, in the sphere of spiritual life. The concept of spirituality, which we have defined as a set of internal spiritual experiences, the richness of the inner world and emotions, is associated with all spheres of society and has an impact on them. Spirituality is expressed in a person’s spirit, character and character. And if not, in other words, spirituality is in every person. Man cannot exist without spirituality. Only its levels are different for everyone. Thus, together with man, spirituality entered all spheres of society. After all, the subject of processes in society is a person, and the object is things and phenomena that arise as a result of human activity. Therefore, you will not find a place in society outside the sphere of influence of spirituality. What does it mean? This means that the impact of every positive update or negative change in spiritual life is reflected throughout society within a short period of time. Alalhus, attention to spiritual life means attention to society as a whole. In the updated policy of Uzbekistan, fundamental changes are taking place in this area. One of the factors hindering the advancement of human spirituality is the coexistence of two forces in the human psyche - good and evil or the forces of good and evil. Because, “A person always carries within himself an infection of some kind of evil spirits. The internal presence of this infection manifests itself in short-term outbreaks of inexplicable horror in a person from time to time. In fact, we all have this evil infection that Søren Kierkegaard described. In our conversations we hear: I didn’t even understand what happened. Something boiled inside me, I didn’t even know what I said or what I did out of anger. Unfortunately, because we don’t know ourselves, we hurt each other and we hurt our hearts. The saddest thing is that this situation sometimes leads to irreparable, very big mistakes. All this happens due to the action of that same evil infection. We can write a lot of information and provide evidence about the negative impact of evil and evil on human life and hindering the progress of society. But more than that, how can you cut off this evil and wickedness? Should man and humanity take measures to avoid them? We would do more useful work if we sought answers to these questions. Although it is difficult to find a satisfactory answer to these questions, let’s try. In our opinion, it is impossible to completely protect humanity from evil and evil, or to completely eliminate them. In the fight against these vices, success can be achieved partially and in certain areas. At the heart of this success is the struggle between a person’s inner self and himself. That is, each person must manifest his Self in the struggle between good and evil or good and evil in his heart. I think this feeling reminds us of our identity in the soul of each of us. I always live in our hearts between good and evil or good and evil. Sometimes he shows his growth under the influence of it, sometimes he shows himself under the influence of it. As we discussed above, it is also affected by unexplained horrors. Moreover, this process is sometimes accomplished by the mind, sometimes by emotions. In order for a person to find the Self in his heart and tear him out of the womb of evil, he needs will, fortitude and patience. Indeed, “if a person does not have a will, he does not have his own Self. However, the stronger the strong will becomes, the more a person is aware of his identity.” Thus, a person who is aware of his identity through the power of will, as he frees himself from the influence of evil, comes to know and understand his Self. Knowing himself means that a person directs himself towards goodness and goodness. How long this process will last depends on the will, determination and endurance of this person. If there is will, the human self will continue to function as good. If he just relaxes, if he can’t stand it, good will give way to evil and everything will start all over again. “As long as life is a high degree of danger,” this process is doomed to repeat itself forever. That is, no one guaranteed that the path of life would be smooth. If we metaphorically compare the life path of each person with dough, then it would be correct to say that his leaven consists of a mixture of good and evil. So, good and evil are in human nature. However, we do not want to conclude this opinion that when babies are born, they can do not only good, but also evil. We only want to say that every child born into this world, as he grows as a human being, has a tendency to do both good and evil. Over time, the environment in the society in which he lives influences the formation of these tendencies in a person from one side or another. REFERENCES Salimov B.L. Expression of Dialectic Categories in the Individual’s Social Life // eu. International Journal of InnovativeAnalyses and Emerging Technology. Volume: 1, lssue 4, 2021. -Р.16-18. Salimov Baxriddin Lutfullaevich. The philosophical role of dialectical categories in human life. Oriental Renaissance: Innovative, educational, natural and social sciences. Volume: 1, lssue 6, 2021. -Р.406-410. Salimov Baxriddin Lutfullaevich. Prospects of Development of Communication and Transport System in Uzbekistan. WEB OF SYNERGY: International Interdisciplinary Research Journal. Volume 2 Issue 2, Year 2023 ISSN: 2835-3013. Salimov, B., Madalimov, T. (2023). Transport falsafasi. Globe Edit. Salimov Bakhriddin Lutfullaevich. The Importance of Sea Transport in the Communication System. WEB OF SYNERGY: International Interdisciplinary Research Journal. Volume 2 Issue 1, Year 2023 ISSN: 2835-3013. Salimov Bakhriddin Lutfullaevich. The Influence of the Transport and Communication System on Social Relations. Web of Semantic: Universal Journal on Ie Education. Volume 2 Issue 2, Year 2023. ISSN: 2835-3048. Salimov Bakhriddin Lutfullaevich. Reforms in the Fields of Communication and Transport and their Social Impact. Web of Semantic: Universal Journal on Ie Education. Volume 2 Issue 2, Year 2023. ISSN: 2835-3048. Салимов Б.Л. Ижтимоий муносабатларнинг коммуникация ва транспорт тизими билан детерминистик боғлиқлигининг гносеологик таҳлили. Фалсафа фанлари доктори диссертацияси. Ўзбекистон Миллий университети. Тошкент. 2022, 224 б. Salimov Bakhriddin Lutfullaevich, Tursunov, Shokhijakhan Ravshanovich, Haydarov, Mehriddin Nuriddin Ugli (2023). SYNERGETIC APPROACH IN THE ANALYSIS OF SOCIAL RELATIONS. Oriental renaissance: Innovative, educational, natural and social sciences, 3 (3), 1001-1007. Bakhriddin Lutfullaevich Salimov. NEGATIVE CONSEQUENCES OF SCIENCE AND TECHNOLOGY DEVELOPMENT. International Conference" Law, Economics and Tourism sciences in the modern world". 2023/5/1. С. 5-10.